An unaccounted fraction of marine biogenic CaCO3 particles. - Mikal Heldal; Svein Norland; Egil S Erichsen; T Frede Thingstad; Gunnar Bratbak (PLoS ONE, 2012)
Biogenic production and sedimentation of calcium carbonate in the ocean, referred to as the carbonate pump, has profound implications for the ocean carbon cycle, and relate both to global climate, ocean acidification and the geological past. In marine pelagic environments coccolithophores, foraminifera and pteropods have been considered the main calcifying organisms. Here, we document the presence of an abundant, previously unaccounted fraction of marine calcium carbonate particles in seawater, presumably formed by bacteria or in relation to extracellular polymeric substances. The particles occur in a variety of different morphologies, in a size range from <1 to >100 µm, and in a typical concentration of 10(4)-10(5) particles L(-1) (size range counted 1-100 µm). Quantitative estimates of annual averages suggests that the pure calcium particles we counted in the 1-100 µm size range account for 2-4 times more CaCO(3) than the dominating coccolithophoride Emiliania huxleyi and for 21% of the total concentration of particulate calcium. Due to their high density, we hypothesize that the particles sediment rapidly, and therefore contribute significantly to the export of carbon and alkalinity from surface waters. The biological and environmental factors affecting the formation of these particles and possible impact of this process on global atmospheric CO(2) remains to be investigated.